Influence of annealing on thermoluminescence of natural quartz: Kinetic analysis and experimental study of apparent inverse thermal quenching. (15th December 2018) - Folley, D.E.; Chithambo, M.L.
Abstract: The influence of annealing on the main thermoluminescence glow-peak of natural quartz is reported. For comparison, results from un-annealed quartz are included. The glow-curve measured at 1 °Cs −1 after beta irradiation to 50 Gy revealed six peaks each for quartz annealed at 800 °C for 1 h and the un-annealed sample. The main peak in both quartzes was observed at 72 °C. This report focusses on kinetic analysis of the main peak. The analysis was carried out using various methods consisting of the initial rise, whole glow-peak, peak shape, variable heating rate and phosphorescence-based methods. The activation energy obtained using the various methods ranges between 0.91 ± 0.01 eV and 1.19 ± 0.03 eV for the annealed sample and between 0.93 ± 0.01 eV and 1.26 ± 0.12 eV for the un-annealed sample. The result suggests that annealing has little effect on the activation energy. The luminescence intensity decreased with heating rate in the un-annealed sample in a manner suggestive of thermal quenching. In contrast, the dependence of intensity on heating rate in the annealed sample is influenced by the dose the sample is irradiated to. Whereas thermal quenching was noted for a dose of 50 Gy in the un-annealed sample, the annealed sample showed evidence of thermal quenching at a low dose of 3 Gy with the opposite effect when irradiated to 50 Gy. The activation energies of thermal quenching were found as 0.89 ± 0.06 eV and 0.99 ± 0.02 eV for the un-annealed and annealed samples respectively. We ascribe the apparent dependence of thermal quenching on dose in the annealed sample to competition between radiative and non-radiative transitions at the recombination centre. Highlights: The influence of annealing on thermoluminescence of natural quartz is reported. Kinetic analysis shows that annealing has little effect on the activation energy. The main peak in un-annealed quartz is affected by thermal quenching. The annealed quartz shows apparent inverse quenching. The sample intensity can be changed to cause inverse quenching to appear.